Modernity, openness, interpretation: a perspective on multiple modernities - Kaya, Ibrahim (2004)
This article aims to inspire an analysis of modernity that would provide a starting point for conceptualizing multiple modernities. First, I argue that conceptualizing modernity as an open-ended horizon engenders spaces to interpret modernity in multiple ways. A view of modernity is thus developed that questions totalizing and Eurocentric theories of modernity. Then the current state of the plurality and diversity of identities and practices is emphasized as the consequence of the openness of modernity to interpretation. In this respect, it is insisted that the different features of non-western cultures should be seen as the indication for the existence of multiple modernities. Finally, for a sociology of multiple modernities, four basic themes are outlines that need to be worked on: plurality of civilizations, histories, modernizing agents and the projects of modernity. - Reproduced.
Keywords: Modernism